What is the role of the surgeon in the management of head and neck mucosal melanoma in the immunotherapy era?. Issue 11 (28th August 2021) - Edmond, Mark; Nenclares, Pablo; Harrington, Kevin; Ap Dafydd, Derfel; Bagwan, Izhar; Begg, Donna; Lingley, Ken; Patterson, Gillian; Payne, Miranda; Steven, Neil; Turnbull, Nancy; Yip, Kent; et al.
Abstract: Introduction: The advent of immunotherapy has impacted both the management and, to a lesser extent, the outcomes for patients with head and neck mucosal melanoma. As a consequence, one might expect that the role of the surgeon would be limited to the diagnostic work‐up and that systemic therapies would be the mainstay of treatment. Methods and Results: Here, we present the surgical aspects of the recently published United Kingdom Head and Neck Mucosal Melanoma Guideline to highlight the continued role of surgeons in the management of this disease. We highlight key areas where surgeons remain the lead clinician and reinforce the multidisciplinary requirement for exemplary patient care. Conclusions: Despite the advent of immunotherapy, surgeons continue to have a key role to play in this disease. When indicated, it is essential that appropriate surgery is offered by a suitably experienced team.